Evaluation of the Collaborative Capability of the Local Government in the Implementation of Collaborative Governance in the Hazardous and Toxic Waste (B3) Control Program in Dumai City - wahyuni, lilis; Rudy Handoko, V; Maduwinarti, Ayun (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
The management of hazardous and toxic waste (B3) presents a major challenge in environmental governance, particularly in industrial areas such as Dumai City. Although regulations such as Dumai City Regional Regulation No. 5 of 2017 have been established, the evaluation of the local government’s collaborative capability in B3 waste control remains suboptimal. This study formulates the research question: how can the collaborative capability of the local government be evaluated in the implementation of Collaborative Governance within the B3 control program in Dumai City? The theoretical framework applied is the Collaborative Capability Evaluation Theory, which consists of four key dimensions: relational, structural, resource, and adaptive capacities. This research employs a qualitative case study approach using interviews, observations, and documentation techniques. The findings indicate that the local government’s collaborative capability is at a moderate level. The main barriers lie in inter-actor trust, inter-agency coordination, and limited resources. Strengthening the four dimensions of collaborative capability is essential to achieving effective, participatory, and sustainable environmental governance in Dumai City.